2001
DOI: 10.1074/jbc.m103766200
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin Scavenges Superoxide in Dopaminergic Neurons

Abstract: Increased oxidative stresses are implicated in the pathogenesis of Parkinson's disease, and dopaminergic neurons may be intrinsically susceptible to oxidative damage. However, the selective presence of tetrahydrobiopterin (BH 4 ) makes dopaminergic neurons more resistant to oxidative stress caused by glutathione depletion. To further investigate the mechanisms of BH 4 protection, we examined the effects of BH 4 on superoxide levels in individual living mesencephalic neurons. Dopaminergic neurons have intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 55 publications
(76 reference statements)
1
64
0
Order By: Relevance
“…Intracellular BH 4 content was reduced by treating cells with inhibitors of BH 4 de novo synthesis. In agreement with a previous report (53) , Fig. 3 (A and B) shows that inhibiting BH 4 synthesis by incubating cells with DAHP (1 mM) and NAS (100 M) for 24 h caused an increase in superoxide generation in CGNs.…”
Section: Resultssupporting
confidence: 80%
“…Intracellular BH 4 content was reduced by treating cells with inhibitors of BH 4 de novo synthesis. In agreement with a previous report (53) , Fig. 3 (A and B) shows that inhibiting BH 4 synthesis by incubating cells with DAHP (1 mM) and NAS (100 M) for 24 h caused an increase in superoxide generation in CGNs.…”
Section: Resultssupporting
confidence: 80%
“…We observed no significant activity differences in any of these enzymes between cell types (Table I). We have previously found tetrahydrobiopterin (BH 4 ), a cofactor for tyrosine hydroxylase, to have antioxidant activity, scavenge superoxide, and protect cells from oxidative stress (28,29). As expected from having a dopaminergic phenotype, MN9D cells had much higher BH 4 levels compared with MN9X (Table I).…”
Section: Differentiated Mn9d Cells Provide An In Vitro Model Of Selecmentioning
confidence: 68%
“…Although it is difficult to separate differences in oxidant production and antioxidant capacities in whole cells, the higher glutathione levels in dopaminergic midbrain neurons compared with non-dopaminergic cells we have previously reported, as well as the presence of tetrahydrobiopterin, a scavenger of superoxide, only in dopaminergic neurons (28,29) likely are significant contributors to this increased antioxidant capacity in dopaminergic neurons. In the present study, we found no differences in activity levels of major antioxidant enzymes between MN9D and MN9X cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is conflicting evidence whether BH 4 is protective or toxic to dopaminergic neurons. Extracellular BH 4 has been shown to increase the rate of apoptotic cell death in DA neurons (Choi et al, 2000;Choi et al, 2003;Kim et al, 2004), while intracellular BH 4 appears to protect DA neurons against oxidative damage (Choi et al, 2003;Nakamura et al, 2001). Treatment of cerebellar granule neurons with sepiapterin attenuated 1-methyl-4-phenylpyridinium-induced (MPP+) toxicity (Shang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%